Towards a comprehensive model of a biofuel supply chain optimization from coffee crop residues. (August 2018) - Chávez, Marcela María Morales; Sarache, William; Costa, Yasel
Highlights: A comprehensive mathematical model is proposed for biofuel supply chain design. We link the three dimensions of sustainability using multiobjective programming. Dynamic capacity strategy in facilities is addressed. A realistic case study in Colombia is conducted. Abstract: Biofuel production from agricultural waste has been identified as a promising strategy in the field of renewable energy. This topic involves complex mathematical modeling tasks such as feedstock characteristics, biorefinery location, capacity strategy and material flows. This paper proposes a Multiple Objective Mixed Integer Linear Programming model (MOMILP) for the design of a sustainable supply chain using multiple agricultural residues. The proposed comprehensive model is utilized in a case study in Colombia, using coffee crop residues. Computational results show the model's robustness as a decision-making tool, which allows the projection of a flexible supply chain structure in the long term.